Terlato Wines International : managing Rutherford Hill merlot in a post-sideways market - Tybout, Alice M.; Bennett, Patrick; Koenigs, Brie ([London] : SAGE, 2016)
In 2005, a wine snob in the critically acclaimed movie 'Sideways' denounced merlot. Subsequently, sales of merlot, including sales for Terlato's Rutherford Hill merlot, declined significantly. Students are asked to evaluate three strategies - rebranding, cutting price, and launching television advertising - that Terlato is considering to reverse this decline.
Originally Published in: Tybout, A.M., Bennett, P., & Koenigs, B. (2008). Terlato Wines International: Managing Rutherford Hill Merlot in a Post-Sideways Market. 5-108-002. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Terlato Wines International (Firm); Marketing -- Case studies; Consumer behavior -- Case studies